Rhabdoid Tumor Predisposition Syndrome: From Clinical Suspicion to General Management - Del Baldo, Giada; Carta, Roberto; Alessi, Iside; Merli, Pietro; Agolini, Emanuele; Rinelli, Martina; Boccuto, Luigi; Milano, Giuseppe Maria; Serra, Annalisa; Carai, Andrea; Locatelli, Franco; Mastronuzzi, Angela (Frontiers in Oncology, 2021)
Rhabdoid tumors are rare aggressive malignancies in infants and young children with a poor prognosis. The most common anatomic localizations are the central nervous system, the kidneys, and other soft tissues. Rhabdoid tumors share germline and somatic mutations in SMARCB1 or, more rarely, SMARCA4, members of the SWI/SNF chromatin-remodeling complex. Rhabdoid tumor predisposition syndrome (RTPS) is a condition characterized by a high risk of developing rhabdoid tumors, among other features. RTPS1 is characterized by pathogenic variants in the SMARCB1 gene, while RTPS2 has variants in SMARCA4. Interestingly, germline variants of SMARCB1 and SMARCA4 have been identified also in patients with Coffin-Siris syndrome. Children with RTPS typically present with tumors before 1 year of age and in a high percentage of cases develop synchronous or multifocal tumors with aggressive clinical features. The diagnosis of RTPS should be considered in patients with rhabdoid tumors, especially if they have multiple primary tumors and/or in individuals with a family history. Because germline mutations result in an increased risk of carriers developing rhabdoid tumors, genetic counseling, and surveillance for all family members with this condition is recommended.